2015
DOI: 10.5152/npa.2015.7410
|View full text |Cite
|
Sign up to set email alerts
|

From Poster Presentation to Publication: National Congress of Child and Adolescent Psychiatry

Abstract: Compared with literature data, it was found that the time to publication was longer while the publication rate was similar for poster presentations in our congresses. Based on these results, it is important to create necessary conditions and encourage the researchers to publish the poster presentations presented in NCCAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
2
9
1
1
Order By: Relevance
“…For total (57%), oral (75%) and poster (52.2%) presentations, anatomy congresses had a higher publication rate than any other clinical sciences ( Table 5 ). Nevertheless, we believe that the number of presented abstracts (161 to 4413) and the number of congresses evaluated (1 to 10) in these studies may have an effect on publication rates ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ). There is another possible reason why the publication rates for some clinical specialties are dramatically lower.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For total (57%), oral (75%) and poster (52.2%) presentations, anatomy congresses had a higher publication rate than any other clinical sciences ( Table 5 ). Nevertheless, we believe that the number of presented abstracts (161 to 4413) and the number of congresses evaluated (1 to 10) in these studies may have an effect on publication rates ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ). There is another possible reason why the publication rates for some clinical specialties are dramatically lower.…”
Section: Discussionmentioning
confidence: 95%
“…The publication rates for these international meetings vary between 0% and 82% ( 2 ). As for national meetings, previous studies focused only on clinical medical sciences with a publication rate ranging between 9.4% and 29.5% ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ). Additionally, we were unable to find studies that evaluated the publication rates of basic medical sciences.…”
mentioning
confidence: 99%
“…Bildirilerin yayın olma özelliklerinin bu önemine rağmen, tıbbın çeşitli branşlarında yapılan çalışmalarda; sunulan özetlerin yayına dönüşme oranlarının %13 ile %74 arasında değişken özellikler gösterdiği görülmektedir (Scherer ve ark. 2006, Özyurt ve Kaptanoğlu 2012, Mutlu ve ark. 2015, Gürses ve ark.…”
Section: Introductionunclassified
“…This study, for the first time, investigated the quality of presentations at the 1 st Congress of the Society of Urological Surgery in Turkiye held in 2012. Previous studies have found publication rates of presentations in congresses in different disciplines, such as rheumatology, dermatology, general surgery, radiology, pediatric psychiatry, orthopedics, plastic surgery and urology, in Turkiye to be ranged between 5.7% and 29.5% (8,9,10,11,12,13,14). In this study, we identified that 28.3% of the presentations at the 1 st Congress of the Society of Urological Surgery in Turkiye were later published in PubMed-indexed journals.…”
Section: Discussionmentioning
confidence: 99%